ECONOMY ASPECT FOR NUCLEAR DESALINATION SELECTION IN MURIA PENINSULA - Sudi Ariyanto; Siti Alimah (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2009)
ABSTRACTECONOMY ASPECT FOR NUCLEAR DESALINATION SELECTION IN MURIA PENINSULA. An assessment of economy aspect for nuclear desalination selection has been carried out. This study compares the costs of water production for the Multi Stage Flash Distillation (MSF), Multi Effect Distillation (MED) and Reverse Osmosis (RO) desalination process coupled to PWR. Economic analysis of water cost are performed using the DEEP-3.1. The results of the performed case study of Muria Peninsula showed that the water cost to desalination process coupled with PWR nuclear power plant (at 5% interest rate, 2750 m3/day capacity, 28oC temperature, 28.700 ppm TDS) with MSF plant is the highest (1.353 /m3), compared to 0.885 /m3 and 0.791 /m3 with the MED and RO plants respectively. As for MSF process, water cost by RO are also sensitive to variables, such as the interest rate, temperature and total salinity. However, MED process is sensitive to interest rate and temperature based on the economic aspect. MSF and MED plants produce a high-quality product water with a range of 1.0 – 50 ppm TDS, while RO plants produce product water of 200 – 500 ppm TDS. Water requirements for reactor coolant system in PWR type is about 1 ppm. Based on economic aspect and water requirements for reactor coolant system in PWR type, so co-generation of PWR and MED may be a favourable option for being applied in Muria Peninsula.Keywords: desalination, RO, MSF, MED, coupling, nuclear power plant, economic ABSTRAKASPEK EKONOMI PADA PEMILIHAN DESALINASI NUKLIR DI SEMENANJUNG MURIA. Kajian aspek ekonomi pada pemilihan desalinasi nuklir telah dilakukan. Studi ini membandingkan biaya produksi air proses desalinasi Multi Stage Flash Distillation (MSF), Multi Effect Distillation (MED) and Reverse Osmosis (RO), yang dikopel dengan PWR. Analisis ekonomi biaya produksi air dilakukan menggunakan DEEP-3.1. Hasil studi kasus yang telah dilakukan di wilayah Semenanjung Muria memperlihatkan bahwa biaya produksi air untuk proses desalinasi yang dikopel dengan PLTN jenis PWR (pada interest rate 5%, kapasitas 2750 m3/hari, suhu 28oC, TDS 28.700 ppm) untuk instalasi MSF adalah paling tinggi (1,353/m3) dibanding instalasi MED (0,885 /m3) dan RO (0,791 /m3). Sebagaimana proses MSF, biaya produksi air RO juga sensitif terhadap variabel, seperti interest rate, suhu dan total salinitas. Namun, proses MED hanya sensitif terhadap interest rate dan suhu. Instalasi MSF dan MED menghasilkan air produk dengan kualitas tinggi dengan kisaran TDS 1-50 ppm, sedangkan RO menghasilkan air produk dengan TDS 200-500 ppm. Persyaratan air untuk sistem pendingin reaktor jenis PWR adalah sekitar 1 ppm. Berdasarkan aspek ekonomi dan persyaratan air untuk sistem pendingin reaktor PWR, maka kogenerasi PWR dan MED dapat menjadi pilihan yang tepat untuk diaplikasikan di Semenanjung Muria.Kata Kunci: desalinasi, RO, MSF, MED, kopel, PLTN, ekonomi